The Effectivity of Planting Media and Fertilizer in Sprouting Ability of Kess (Lophostemon suaveolens (Sol.ex Gaertn.) Peter G.Wilson & J.T. Waterh) Stool Plant) - Dwi Kartikaningtyas; Teguh Setyaji; NFN Surip (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
The need for large-scale seedlings is needed to support the speed-up of land rehabilitation among others on peatlands. To reach the needs, appropriate techniques are needed, as well as the appropriate of stool plant as a provider of vegetative propagation genetic material. The purpose of the study was to determine the influence of the planting media and the application of various types of fertilizer on Kess (Lophostemon suaveolens) stool plant in shoots growth and shoots length. The research was designed by using the Completely Randomized Design (CRD) with 2 x 3 factorial design on two types of planting media (sand, cocopeat) and three types of fertilizer (slow release , compound and leaf fertilizer). The results showed that the planting media gave a real effect to the shoots growth and increasing of shoots length, however the application of fertilizer only had an effect on shoots growth. The combination of sand medium and controlled release fertilizer has more effective compared to other combinations.